Controversial Terminology: Medieval Perspectives on Claiming and Assigning Imperial Status. (October 2017) - Jones, Chris; Mauntel, Christoph; Oschema, Klaus
In recent years, research on the concept of 'empire' has seen an upswing of interest in both Political Science and History. Definitions of 'empire' abound, as they do for words such as 'discourse', 'performance' and 'culture'. Countless books and edited volumes concerning questions of 'empire' have been published since the turn of the century. On the most general level, however, the majority of studies on questions of 'empire' tend to neglect the European Middle Ages. Medievalists continue to associate the Latin terms imperium and imperator primarily with the (Holy) Roman Empire. A closer examination of the existing material in Latin and the vernacular languages reveals that many late medieval authors were far from limited in their use of imperial terminology. This introductory essay establishes the historiographical context for an exploration of this terminology as it was employed in the Latin West in two instances. The first is imperial self-designation, cases where rulers explicitly adopted or avoided the language of empire in referring to themselves or their realms. The second is the use of imperial terminology by authors from Latin Europe to describe and characterise distant and foreign regions of the world.